Wpływ wdrożenia systemu zarządzania przez wartość na organizacyjne uczenie się - na przykładzie firmy Systemy IT - Czarnecki, Maciej (Value based management system impact on organizational learning (based on the systemy IT case study), 2006)
VBM as a new trend, mainly in the fields of strategic management and corporate finance management, has become a frequent topic of discussions in academic environment, as well as among managers and consultants. It impacts not only areas mentioned above, but also all the areas of companies’ lives, including marketing, selling, motivation, goods storage etc. Due to prof. A. Rappaport, one of the pioneers of the VBM idea, there is a big chance that it will become a standard in a couple of years. Learning organization is another new trend, which emphasizes the role of learning in the organization. The article shortly introduces case study, which is an example of the positive influence of the value based management system on the organizational learning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 37-42